Polarization Sensitive Array Beamforming Algorithm for Multipath Mitigation in GNSS - Wang, Xiaojian; Li, Jianxing; Zhang, Ming; Chen, Wenchao; Chen, Xiaoming (2020 IEEE 3rd International Conference on Electronic Information and Communication Technology (ICEICT), 2020)
In this paper, the polarization sensitive array is proposed to mitigate the multipath reflections in global navigation satellite systems (GNSS). The minimum variance distortionless response (MVDR) and the multiple signal classification (MUSIC) algorithms are used to estimate the directions and polarization of the signal and the multipath reflections. By using the estimated information, the linear constrained minimum variance (LCMV) beamformer maximizes the signal, meanwhile, nulls the multipath reflections, in both spatial and polarization domains.